Advancing emergency department–initiated buprenorphine - Kristen Huntley; Emily Einstein; Terri Postma; Anita Thomas; Shari Ling; Wilson Compton (Journal of the American College of Emergency Physicians Open)
Abstract Opioids are the main driver of drug overdose deaths in the United States, and there has been a marked increase in opioid‐related overdoses during the COVID‐19 public health emergency. Many emergency departments (EDs) across the country are implementing ED‐initiated buprenorphine programs, and this is a method to address and prevent opioid overdoses. Resources are available to overcome barriers and take action.